2000
DOI: 10.4319/lo.2000.45.1.0246
|View full text |Cite
|
Sign up to set email alerts
|

Calcification does not stimulate photosynthesis in the zooxanthellate scleractinian coral Stylophora pistillata

Abstract: The interaction between photosynthesis and calcification remains poorly known in zooxanthellate scleractinian corals. We tested whether calcification is a significant source of CO2 for photosynthesis in Stylophora pistillata. Rates of net photosynthesis, respiration, and calcification were measured on colonies incubated in synthetic seawater (SSW) controlled with respect to the inorganic carbon system and containing standard (11.40 mmol kg−1) and low (2.85 mmol kg−1) calcium concentrations. Net photosynthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 13 publications
5
34
1
Order By: Relevance
“…The Gattuso et al (2000) experiment also revealed that the reduced calcification observed for the zooxanthellate scleractinian coral Stylophora pistillata reared under low-[Ca 2+ ] conditions was not accompanied by reduced photosynthesis. Thus, in contrast to some species of bryopsidalean (Ries, 2005a(Ries, , 2006a(Ries, , 2009Stanley et al, 2010) and coccolithophorid algae (Stanley et al, 2005), calcification appears not to stimulate photosynthesis within zooxanthellate scleractinian corals.…”
Section: Effect Of Absolute [Ca 2+ ] On Calcification Rates Within Scmentioning
confidence: 78%
See 1 more Smart Citation
“…The Gattuso et al (2000) experiment also revealed that the reduced calcification observed for the zooxanthellate scleractinian coral Stylophora pistillata reared under low-[Ca 2+ ] conditions was not accompanied by reduced photosynthesis. Thus, in contrast to some species of bryopsidalean (Ries, 2005a(Ries, , 2006a(Ries, , 2009Stanley et al, 2010) and coccolithophorid algae (Stanley et al, 2005), calcification appears not to stimulate photosynthesis within zooxanthellate scleractinian corals.…”
Section: Effect Of Absolute [Ca 2+ ] On Calcification Rates Within Scmentioning
confidence: 78%
“…Other experiments on specimens of Acropora sp., Stylophora pistillata, Acropora cervicornis and Acropora formosa show that calcification rates increase as Ca 2+ concentrations are elevated from approximately 20% to 80% of normal marine values (Chalker, 1976;Gattuso et al, 1998Gattuso et al, , 2000. At Ca 2+ concentration above 80%, calcification rates level out and, in some cases, decline.…”
Section: Effect Of Absolute [Ca 2+ ] On Calcification Rates Within Scmentioning
confidence: 99%
“…Calcification rates have been observed to be higher in light than in dark (e.g., Kawaguti and Sakumoto 1948), suggesting photosynthetic stimulation of calcification. The opposite interaction, i.e., stimulation of photosynthesis by calcification, has also been suggested in several studies (McConnaughey 1991;McConnaughey and Whelan 1997), though Gattuso et al (2000) argued that CO 2 released by calcification was not a significant source for algal photosynthesis. Suzuki et al (1995) simulated a model of coexisting effects of photosynthesis and calcification and showed that both reactions potentially enhance each other.…”
mentioning
confidence: 96%
“…mixotrophy | zooxanthella | coral bleaching | food web | Heterosigma C orals in the ocean have drawn much attention from scientists, tourists, fishermen, and government officials (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Freeliving and symbiotic dinoflagellates in the genus Symbiodinium (also known as zooxanthellae) were once considered exclusively photosynthetic, except for the uptake of dissolved organic materials (17).…”
mentioning
confidence: 99%